The Effect of Problem-Based Learning with Map Props on Fifth-Grade Students’ Cultural Literacy - Ika Hikmah; Herniyanti Herniyanti (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to examine the effect of the Problem-Based Learning (PBL) model assisted by map props on the cultural literacy of fifth-grade students at SDN 1 Rejosari. A quantitative approach was employed using a quasi-experimental design with a pretest–posttest control group. The sample consisted of 38 students, divided into two groups: an experimental group and a control group, each with 19 students. An essay-based test was used to measure students' cultural literacy before and after the instructional intervention. Data were analyzed using prerequisite tests, an independent-samples t-test, and N-Gain analysis. The results showed that the experimental group achieved an average N-Gain of 53.23%, which was categorized as moderate. In comparison, the control group achieved an average N-Gain of 11.16%, which was categorized as low. The t-test results indicated a significance value of 0.000 (p < 0.05), demonstrating a statistically significant difference between the two groups. It can be concluded that implementing the PBL model, supported by map media, is effective in improving students' cultural literacy through active, contextual, and meaningful learning, thereby enhancing their understanding and awareness of cultural diversity.